1979
DOI: 10.1111/j.1476-5381.1979.tb07853.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Pancuronium‐induced Super‐sensitivityto Noradrenaline in Rat Smooth Muscle

Abstract: Pancuronium bromide (5 × 10−5m) caused super‐sensitivityto noradrenaline in the rat isolated vas deferens and hepatic portal vein. This super‐sensitivitywas manifest as a parallel leftward shift of the dose‐response curve for noradrenaline with no alteration of the maximum response to the agonist. Pancuronium did not potentiate the response of the vas and portal vein to St 91, anα‐adrenocep‐tor agonist which is not a substrate for Uptake x. Pancuronium did not potentiate the response of the vas to CaCl2. In va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Several groups of workers have shown that pancuronium blocks noradrenaline reuptake into sympathetic nerve endings (Uptake 1) both in cardiac muscle and in smooth muscle of guineapigs and rats (Ivankovich et al, 1975;McGrath, 1977, 1978;Quintana, 1977;Marshall and Ojewole, 1979;Tomlinson, 1979;Salt, Barnes and Conway, 1980). Fazadinium also produces this effect, but tubocurarine, meto-curine and gallamine do not, and Org NC45 is considerably less effective than pancuronium in this respect (Marshall and Ojewole, 1979;Docherty and McGrath, 1980;Marshall, McGrath et al, 198,0).…”
Section: Block Of Noradrenaline Uptake Processesmentioning
confidence: 99%
“…Several groups of workers have shown that pancuronium blocks noradrenaline reuptake into sympathetic nerve endings (Uptake 1) both in cardiac muscle and in smooth muscle of guineapigs and rats (Ivankovich et al, 1975;McGrath, 1977, 1978;Quintana, 1977;Marshall and Ojewole, 1979;Tomlinson, 1979;Salt, Barnes and Conway, 1980). Fazadinium also produces this effect, but tubocurarine, meto-curine and gallamine do not, and Org NC45 is considerably less effective than pancuronium in this respect (Marshall and Ojewole, 1979;Docherty and McGrath, 1980;Marshall, McGrath et al, 198,0).…”
Section: Block Of Noradrenaline Uptake Processesmentioning
confidence: 99%